2016
DOI: 10.17586/2220-8054-2016-7-1-44-50
|View full text |Cite
|
Sign up to set email alerts
|

Is graphane the most stable carbon monohydride?

Abstract: We discuss a number of hydrocarbon structures whose cohesive energy is not worse than that of benzene and graphanes. These structures can be regarded as sublattices of known carbon structures so the strain exerted on the crystal lattice is minimal and caused mostly by the steric interactions of hydrogen atoms. Possible synthetic routes are proposed. Due to their exceptional mechanical, structural and electrical properties, these crystal structures may have utility as mechanical, optoelectronic or biological ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…As discussed in Section 3.1 , diamond lattice can be paved in 3D by backbones of diamantane molecules. It was previously shown that diamond lattice can be divided into two interpenetrating networks [ 39 , 40 , 41 ] of carbon atoms. Each of these networks can be regarded as the carbon backbone of crystal polymeric hydrocarbon named diamond monohydride.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in Section 3.1 , diamond lattice can be paved in 3D by backbones of diamantane molecules. It was previously shown that diamond lattice can be divided into two interpenetrating networks [ 39 , 40 , 41 ] of carbon atoms. Each of these networks can be regarded as the carbon backbone of crystal polymeric hydrocarbon named diamond monohydride.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the crucial step of this reaction is the formation of one diamantane molecule from two adamantanes: As discussed in Section 3.1, diamond lattice can be paved in 3D by backbones of diamantane molecules. It was previously shown that diamond lattice can be divided into two interpenetrating networks [39][40][41] of carbon atoms. Each of these networks can be regarded as the carbon backbone of crystal polymeric hydrocarbon named diamond monohydride.…”
Section: A Synthesis Mechanismmentioning
confidence: 99%
“…Variation in the width of nanoribbons made of allotropic graphene can be used to control the band gap [105]. The thermodynamic stability of crystallographic allotropic forms and functionalized graphene has been studied in [106][107][108][109].…”
Section: Dependencementioning
confidence: 99%